2014
DOI: 10.1213/ane.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Continuous Noninvasive Hemoglobin Monitoring

Abstract: Although the mean difference between noninvasive Hb and central laboratory measurements was small, the wide limits of agreement mean clinicians should be cautious when making clinical decisions based on these devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
4
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 55 publications
3
61
4
2
Order By: Relevance
“…Recent studies conducted to validate NBM 200 mainly involved blood donation centres within hospital settings 4. There is a strong clinical need to measure Hb levels accurately in settings where laboratory access is not easy, particularly during pregnancy where repeated measurements are required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies conducted to validate NBM 200 mainly involved blood donation centres within hospital settings 4. There is a strong clinical need to measure Hb levels accurately in settings where laboratory access is not easy, particularly during pregnancy where repeated measurements are required.…”
Section: Introductionmentioning
confidence: 99%
“…There is a strong clinical need to measure Hb levels accurately in settings where laboratory access is not easy, particularly during pregnancy where repeated measurements are required. However, there are no published evidences on the application of non-invasive Hb sensors outside hospital settings for antenatal anaemia screening 2 4. Thus, it is an important area of research considering the high prevalence of anaemia in women during pregnancy in a country like India 5 6.…”
Section: Introductionmentioning
confidence: 99%
“…For continuous through-the-skin optical noninvasive Hb monitoring (NIHb or SpHb), portable bedside equipment (e.g. within operating rooms or intensive care units) also is already on the market, but accuracy presently still needs improvement [44,45]. The optical measurement principle is strongly related to pulse oximetry, and it is likely that over the coming years throughthe-skin Hb-measurement accuracy can be further improved and miniaturized to pocket size (for periodic Hb-check).…”
Section: Anemia (4/23)mentioning
confidence: 99%
“…Several studies have indicated that SpHb provides values comparable to laboratory Hb for both absolute and changes in hemoglobin values, while others have suggested SpHb is unreliable and correlates poorly with laboratory Hb [12][13][14][15][16][17][18][19][20][21]. In spite of its limitations, continuous SpHb monitoring may provide useful real-time information to the anesthesiologist during the transfusion decision making process, perhaps by making Hb trend data visible.…”
Section: Introductionmentioning
confidence: 99%